Automated Facial Recognition for Noonan Syndrome Using Novel Deep Convolutional Neural Network With Additive Angular Margin Loss - Yang, Hang; Hu, Xin-Rong; Sun, Ling; Hong, Dian; Zheng, Ying-Yi; Xin, Ying; Liu, Hui; Lin, Min-Yin; Wen, Long; Liang, Dong-Po; Wang, Shu-Shui (Frontiers in Genetics, 2021)
Background: Noonan syndrome (NS), a genetically heterogeneous disorder, presents with hypertelorism, ptosis, dysplastic pulmonary valve stenosis, hypertrophic cardiomyopathy, and small stature. Early detection and assessment of NS are crucial to formulating an individualized treatment protocol. However, the diagnostic rate of pediatricians and pediatric cardiologists is limited. To overcome this challenge, we propose an automated facial recognition model to identify NS using a novel deep convolutional neural network (DCNN) with a loss function called additive angular margin loss (ArcFace). Methods: The proposed automated facial recognition models were trained on dataset that included 127 NS patients, 163 healthy children, and 130 children with several other dysmorphic syndromes. The photo dataset contained only one frontal face image from each participant. A novel DCNN framework with ArcFace loss function (DCNN-Arcface model) was constructed. Two traditional machine learning models and a DCNN model with cross-entropy loss function (DCNN-CE model) were also constructed. Transfer learning and data augmentation were applied in the training process. The identification performance of facial recognition models was assessed by five-fold cross-validation. Comparison of the DCNN-Arcface model to two traditional machine learning models, the DCNN-CE model, and six physicians were performed. Results: At distinguishing NS patients from healthy children, the DCNN-Arcface model achieved an accuracy of 0.9201±0.0138 and an area under the receiver operator characteristic curve (AUC) of 0.9797±0.0055. At distinguishing NS patients from children with several other genetic syndromes, it achieved an accuracy of 0.8171±0.0074 and an AUC of 0.9356±0.0066. In both cases, the DCNN-Arcface model outperformed the two traditional machine learning models, the DCNN-CE model, and six physicians. Conclusion: This study shows that the proposed DCNN-Arcface model is a promising way to screen NS patients and can improve the NS diagnosis rate.